Integrated of Local Wisdom-Based Character Through Social Studies Learning - Dona Eka Lovanie (Social Studies Conference Proceedings, 2022)
Cultivation of character benefits individual growth towards a community environment, a place that provides comprehensive services related to this in educational institutions. Instilling character through schools can be optimized using local wisdom because it contains values ​​that encourage character cultivation. Introducing local wisdom to students is also an effort to increase insight into local culture to avoid a situation of cultural erosion against the flow of globalization. One goal of social studies learning is to develop the potential of students to be sensitive to social problems in society. Therefore individuals need to have good ethics and morals and love the universe, which can be obtained through social studies learning based on local wisdom. This article aims to describe the importance of planting characters based on local wisdom in social studies learning using learning methods and models designed by teachers through various relevant sources. Social studies learning oriented to local wisdom can become a shield for the flow of globalization and the ability to take care of oneself through an attitude ingrained based on the values ​​​​of local wisdom so that it can strengthen social competence.